2018
DOI: 10.1186/s41073-018-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and supervisors’ knowledge and attitudes regarding plagiarism and referencing

Abstract: BackgroundReferencing is an integral part of scientific writing and professional research conduct that requires appropriate acknowledgement of others’ work and avoidance of plagiarism. University students should understand and apply this as part of their academic development, but for this, it is essential that supervisors also display proper research integrity and support.MethodsThis study used an online educative questionnaire to understand the knowledge and attitudes of students and supervisors at two instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…One recent comparative study conducted among students and their supervisors with the aim of assessing knowledge and attitudes concerning referencing and plagiarism has revealed that responses of the students reflect their differing backgrounds. In particular, Western Europeans and North Americans showed better understanding of the nature of plagiarism than did other nationalities (Lindahl & Grace, 2018).…”
Section: Academic Writing and Plagiarismmentioning
confidence: 91%
“…One recent comparative study conducted among students and their supervisors with the aim of assessing knowledge and attitudes concerning referencing and plagiarism has revealed that responses of the students reflect their differing backgrounds. In particular, Western Europeans and North Americans showed better understanding of the nature of plagiarism than did other nationalities (Lindahl & Grace, 2018).…”
Section: Academic Writing and Plagiarismmentioning
confidence: 91%
“…This early training enables students to be progressively involved in "real life" research work through projects and publications and to start building their professional network. By contrast, mentoring from experienced colleagues is not always available at institutions in low-income countries, resulting in a wide variation in research quality and visibility [3]. This is especially true in French-speaking West Africa where research is highly fragmented and collaborative work culture is lacking, including at the national and regional levels.…”
Section: Rationale and Aim Of The Mooscitic Projectmentioning
confidence: 99%
“…Failure to 'cite' is cheating, which may be either intentional and unintentional. 5 The accuracy of content cited must match the content in the reference. Citation based on title and abstract, without reading the original article for the details of design, and process of their findings may result in errors and it is irritating when one cannot find the information in cited reference.…”
Section: Figure 1 Cycle Of Research-writing-publicationmentioning
confidence: 99%
“…Appropriate referencing, and need for more training is necessary for both students and faculties. 5,7,8 Rapid growth of science has led to proliferation of scientific journals contributing to medical literature. With various referencing styles, manually referencing is labor intensive.…”
Section: Figure 1 Cycle Of Research-writing-publicationmentioning
confidence: 99%